In Vitro Free Radical Scavenging Activity Of Various Root And Rhizome Extracts Of Acorus Calamus Linn - A.ELAYARAJA; M.VIJAYALAKSHMI; G.DEVALARAO (International Journal of Pharma and Bio Sciences, 2010)
Consecutive ethanolic and hydro alcoholic extracts of roots and rhizomes of Acorus calamus Linn (Araceae) were prepared and investigated for antioxidant potential against 2,2 diphenyl-1picrylhydrazyl (DPPH) free radicals and compared with butylatedhydroxyanisole (BHA) and silymarin. Cumulative concentrations of both the extracts showed free radical scavenging activity of 59.13 ± 18.95 and 56.71 ± 19.54 respectively. It was also concluded that ethanolic extract showed the maximum antioxidant activity. Also increase in concentration of the extract showed enhance in free radical scavenging activity.